Early acetabular cup migration may be a source of error in the assessment of intra-operative placement accuracy - Taleb, Shahnaz; Polus, Jennifer S.; Lanting, Brent; Teeter, Matthew G. (Journal of Orthopaedic Reports, 2025)
Proper alignment of the acetabular cup is essential for long-term success total hip arthroplasty (THA) success. Computer navigation and robotic techniques have been of interest to improve cup alignment, with their accuracy often reported by comparing the intraoperative alignment to six-week postoperative alignment; however, early component migration is known to occur within the first six weeks. This study aimed to assess the potential error in cup position measurements caused by early acetabular cup migration within the first six weeks following THA. Acetabular cup inclination and anteversion angles were measured by two raters from radiographs taken intra-operatively and at six weeks post-operation. An RSA examination was performed on the day of surgery as well as 6-weeks post-operation. Thirty-three patients were included in our analysis. Mean inclination angles were 31.2° intra-operatively and 32.8° at six weeks post-operation (maximum difference = 11.1°). Mean anteversion angles were 23.5° and 29.3° intra-operatively and at six weeks post-operation (maximum difference = 15.3°). Mean anterior tilt, internal rotation, and valgus rotation between the day of surgery and six weeks post-operation were 1.33°, 0.98°, and 0.80°, respectively. This study demonstrated that early migration of acetabular cups may introduce an error in studies reporting computer navigation accuracy in acetabular cup placement based on post-operative imaging follow-ups.